Colorado water, March/April 2019 - Boehmer, Catie, editor; Colorado Water Center, publisher (Colorado State University. Libraries, 2019)
Newsletter of the Colorado Water Center. Theme: Data-driven water management.
The newsletter is devoted to highlighting water research and activities at CSU and throughout Colorado.
Keywords: Water resources development -- Colorado; Water use -- Colorado; Water-supply -- Colorado; Water-supply -- Management -- Colorado